2014
DOI: 10.3389/fimmu.2013.00514
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin/Txnip: Redoxisome, as a Redox Switch for the Pathogenesis of Diseases

Abstract: During the past few decades, it has been widely recognized that Reduction-Oxidation (redox) responses occurring at the intra- and extra-cellular levels are one of most important biological phenomena and dysregulated redox responses are involved in the initiation and progression of multiple diseases. Thioredoxin1 (Trx1) and Thioredoxin2 (Trx2), mainly located in the cytoplasm and mitochondria, respectively, are ubiquitously expressed in variety of cells and control cellular reactive oxygen species by reducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
282
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(287 citation statements)
references
References 110 publications
5
282
0
Order By: Relevance
“…Several studies have indicated that a disturbance in the redox state of an organism leads to aging and age-related diseases [3537]. Due to these unique features, Trx, along with thioredoxin interacting protein (Txnip), has been shown to play very important roles in physiology and its dysregulation could be involved in various diseases [38]. However, the roles of Trx on aging and age-related pathology in mammals have not fully been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that a disturbance in the redox state of an organism leads to aging and age-related diseases [3537]. Due to these unique features, Trx, along with thioredoxin interacting protein (Txnip), has been shown to play very important roles in physiology and its dysregulation could be involved in various diseases [38]. However, the roles of Trx on aging and age-related pathology in mammals have not fully been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TxNIP inhibits the thioredoxin system, which is a key antioxidant system that protects cells from oxidative stress through its disulfide reductase activity [53]. It was previously shown that ER stress increases TxNIP levels through induction of IRE1α activity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the α-arrestin family member Trx-interacting protein (TXNIP) seems to integrate glucose availability and ROS. As its name indicates, TXNIP forms intermolecular disulfi des with Trx, inhibiting it and promoting oxidative stress [ 36 ]. TXNIP furthermore regulates the glucose transporter Glut1 by suppressing Glut1 mRNA and promoting its internalization via clathrin-coated pits.…”
Section: Biochemical Mechanisms That Preserve Redox Homeostasismentioning
confidence: 99%